Cutaneous mosaicisms: concepts, patterns and classifications - Samara Silva Kouzak; Marcela Sena Teixeira Mendes; Izelda Maria Carvalho Costa (Sociedade Brasileira de Dermatologia, 2013)
A mosaic is an organism composed of two or more genetically distinct cell populations derived from a genetically homogeneous zygote. Cutaneous mosaicisms are the clinical expressions of these disorders. The main event which allows the existence of mosaicism is a genetic mutation, either structural or functional. Cutaneous mosaicisms usually manifest by specific patterns on the skin and the archetypic pattern is the system of Blaschko lines, but others include checkerboard, phylloid, large patches without midline separation and lateralization. Since 1901, when Blaschko lines were first described, the study of mosasicism has helped to elucidate the behavior of numerous genetic diseases, generating therapeutic perspectives for these pathologies, including the promising gene therapy.